THE ROLE OF FAMILY SUPPORT ON POSTNATAL MOTHERS' MENTAL WELLBEING: A LITERATURE REVIEW - Dewi Hestiani K; Fardi, Fardi (Media Inovasi Pendidikan dan Publikasi, 2023)
Postpartum maternal mental well-being is a critical aspect of public health, affecting the quality of life for mothers, infants, and families. This article presents a systematic literature review on the role of family support in postpartum maternal mental health. Using the PRISMA method, searches were conducted in major databases such as PubMed, Scopus, and Google Scholar under defined inclusion criteria. Results indicate that family support, including emotional, instrumental, and overall social support, significantly reduces the risk of mental health issues like postpartum depression. Emotional support fosters feelings of appreciation and alleviates anxiety, while instrumental support reduces physical burdens through practical assistance, such as childcare. Additionally, social support within collectivist cultures provides a supportive environment that enhances maternal psychological well-being. Conversely, a lack of family support is associated with increased symptoms of depression and anxiety. These findings highlight the importance of a holistic approach involving families and communities to promote postpartum maternal mental well-being. Community-based interventions, such as family training and couple counseling, can enhance the effectiveness of this support. Collaborative efforts are thus essential to creating supportive family environments to ensure postpartum maternal mental health.